2024
DOI: 10.1051/0004-6361/202346656
|View full text |Cite
|
Sign up to set email alerts
|

Lyman continuum leaker candidates at z ∼ 3–4 in the HDUV based on a spectroscopic sample of MUSE LAEs

J. Kerutt,
P. A. Oesch,
L. Wisotzki
et al.

Abstract: In recent years, a number of Lyman continuum (LyC) leaker candidates have been found at intermediate redshifts, providing insight into how the Universe was reionised at early cosmic times. There are now around 100 known LyC leakers at all redshifts, which enables us to analyse their properties statistically. Here, we identify new LyC leaker candidates at $z 3-4.5$ and compare them to objects from the literature to get an overview of the different observed escape fractions and their relation to the propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 221 publications
0
1
0
Order By: Relevance
“…) has been detected by Naidu et al (2018) in a stack of extreme [O III] emitters (a "Green Pea" subgroup known to have an elevated fesc,H at low redshifts; e.g., Izotov et al 2018) or in low-mass lensed galaxies at 1.3 z 3.0 (Jung et al 2024). In a sample of 621 Lyαemitting galaxies at z = 3.0-4.5, Kerutt et al (2024) recently identified only 5 likely LyC leakers but argued that this detection rate was consistent with a global escape fraction of 12%. Using an alternative approach to constrain fesc,H empirically at 1.6 < z < 6.7 via spectroscopy of long-duration gamma-ray burst afterglows, Tanvir et al (2019) estimated an average escape fraction of 0.7% at the Lyman limit.…”
Section: Introductionmentioning
confidence: 99%
“…) has been detected by Naidu et al (2018) in a stack of extreme [O III] emitters (a "Green Pea" subgroup known to have an elevated fesc,H at low redshifts; e.g., Izotov et al 2018) or in low-mass lensed galaxies at 1.3 z 3.0 (Jung et al 2024). In a sample of 621 Lyαemitting galaxies at z = 3.0-4.5, Kerutt et al (2024) recently identified only 5 likely LyC leakers but argued that this detection rate was consistent with a global escape fraction of 12%. Using an alternative approach to constrain fesc,H empirically at 1.6 < z < 6.7 via spectroscopy of long-duration gamma-ray burst afterglows, Tanvir et al (2019) estimated an average escape fraction of 0.7% at the Lyman limit.…”
Section: Introductionmentioning
confidence: 99%